Delayed diagnosis, advanecement and results of treatment of pancreatic cancer - Jesipowicz, Jacek; Piłat, Jacek; Jesipowicz, Mieczysław; Matras, Przemysław; Rudzki, Sławomir (Contemporary Oncology/Współczesna Onkologia, 2000)
Carcinoma of pancreas is an unsolved problem in pancreatic surgery. It is assumed that less than 20% of patients do not survive 1 year after the diagnosis. The aim of the present study is to present cancer advancement, the possibility of radical treatment and the results of treatment in two groups: with and without postoperative chemiotherapy. There were 114 patients operated on for pancreatic cancer. Resective operations were performed on 49 patients: 26 standard Whipple pancreato-duodenectomies, 10 extended Whipple procedures, 4 total pancreatoduodenectomies with splenectomy, 9 distal resections – body and tail of pancreas with splenectomy and removal of surrounding tissue. The other patients were not qualified for resectional operation: 34 underwent by-pass operations and as many as 31 for sxploratory laparotomy. In the group treated between 1996-98 in 13 patients postoperative chemotherapy was introduced. Patients’ survival who underwent resectional procedure ranged from 7 to 42 months. Survival of patients who underwent by-pass operations ranged from 8 to 14 weeks and median survival of patients after exploratory laparotomy was 6 weeks. We do not find clear dependence of the length of the survival on the chemotherapy applied. On the basis of our material we can conclude that patients are admitted with advanced pancreatic neoplasm process. Extended procedure allowed to achieve slight increase in median survival. It seems that early diagnosis can increase 5-year survival.